Relationship of forward head posture and cervical backward bending to neck pain. - Haughie LJ; Fiebert IM; Roach KE (Journal of Manual & Manipulative Therapy (Journal of Manual & Manipulative Therapy), 1995)
The purpose of this study was to investigate the relationship of forward head posture and cervical backward bending to neck pain. The subjects were fifty-four volunteer office workers, who spent at least four hours of their work day at a computer terminal (17 males and 37 females). Since all subjects reported having pain, the subjects who reported pain in four areas or more were considered the case group and those who reported pain in three areas or less were considered the control group. Measurements of forward head posture and cervical backward bending in both the natural sitting position and the erect sitting position were recorded by the Cervical Range of Motion Instrument (CROM). The results showed that compared to the control group, the case group subjects had more pain over the past thirty days, visited medical professionals more frequently during the past twelve months, and when describing a typical day reported greater pain. Additionally, members of the case group had greater forward head posture and less cervical backward bending in the natural sitting position and the erect sitting position. The results of this study support the belief that a relationship of forward head posture and cervical backward bending to neck pain exists.